PENINGKATAN KOMPETENSI GURU SEKOLAH LUAR BIASA DALAM PEMBELAJARAN INOVATIF BERBASIS TIK - Darmawan, I.D.M.B.A (Buletin Udayana Mengabdi, 2023)
Educational transformation can be carried out by utilizing information technology in all activities of implementing learning in schools. This paper is the complete service at SLB N 2 Denpasar, which aims to provide an understanding of ICT-based Innovative learning. The service is carried out through training methods that provide education staff and teachers with an understanding of the use of cloud computing technology and various e-assessment methods to increase teachers' understanding of the use of Classroom as a Learning Management System. The training, carried out for 3 days, could run well by applying the collaborative method. The questionnaire results increase the understanding of the use of ICT in learning, and the material provided can improve work. Keywords: education transformation, elearning, classroom, cloud computing, tik, slb